PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KURIKULUM 2013 MELALUI PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) PADA MATERI KUBUS BALOK SMP/MTs - Zuli Rahayu; Kartini '; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study is the restrict of mathematics learning instruments as supporting learning referring to  Curriculum 2013 and weak ability of teachers to develop the mathematics learning instruments corresponding with curriculum 2013. This study aimed to develop mathematics learning instruments based curriculum 2013 with approach mathematics learning Realistic Mathematics Education (RME) on the material cubes and blocks for students of class VIII SMP/MTs. Learning instruments in this study are lesson plan, and the Student Activity Sheet. This study method used is 4D model by Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel that consist of define, design, development, and disseminate, but the study was limited only to development step. Based on the results of data analysis can be concluded that the study of mathematics is very valid to the average ratings for the lesson plan is 3.71 and the average ratings for the student activity sheet is 3.69. This student worksheet has also reached the practical qualification with mean percentage of student responses 97% in the small group trial and 97% in the large group trial.